STRATEGI MARKETING POLITIK ANGGOTA LEGISLATIF PEREMPUAN LILIS NURLIA DAN EKA WIDYANI LATIEF PADA PEMILU 2019 DI KOTA BEKASI DARI PARTAI KEADILAN SEJAHTERA (PKS) - Wiji Setiyani (2022)
This paper aims to find out the political marketing carried out by women's legislators Lilis Nurlia and Eka Widyani Latief from the Partai Keadilan Sejahtera (PKS) in the 2019 election in Bekasi City using Philip B. Niffenegger's political marketing theory and Harris' modern political marketing and Kapferer's political branding. The research method used is qualitative research with a case study approach to finding an overview of experiences regarding political marketing strategies carried out by women's legislators Lilis Nurlia and Eka Widyani Latief from the Partai Keadilan Sejahtera (PKS) is facing the 2019 elections in Bekasi City. The data obtained in this paperusesg primary and secondary data. Primary data was obtained from information from the informant Lilis Nurlia and her Success Team, Eka Widyani Latief, and the people who chose Lilis Nurlia and Eka Widyani Latief. Interviews were conducted using semi-structured interview techniques. Meanwhile, the secondary data used comes from books, journals, news articles on social media, and file archives from the KPU Provinsi Jawa Barat and KPUD Kota Bekasi. The results showed that female legislators Lilis Nurlia and Eka Widyani Latief from the Partai Keadilan Sejahtera (PKS) in implementing political marketing strategies according to Philip's political marketing theory B. Niffenegger can be said to run well by implementing Product, Price, Promotion, and Place. Then Harris' modern political marketing theory carried out by Lilis Nurlia can be applied properly while Eka Widyani Latief still has shortcomings which can be seen from the level of public relations run by Eka Widyani Latief is not too active. Although both are more focused on face-to-face media than social media. Furthermore, the Kapferer political branding theory was successfully applied by Lilis Nurlia and Eka Widyani Latief from the Partai Keadilan Sejahtera (PKS).